Family Islamic Religious Education and Children's Interest in School Religious Activities: Evidence From Gunung Sari Village Pesawaran - Aminudin, Dzihab_aminudin (TA`DIBUNA, 2025)
This study aims to examine the influence of Islamic religious education within the family on children's interest in participating in religious activities at school in Gunung Sari Village, Way Khilau, Pesawaran, Lampung. The background of the study is based on the crucial role of the family as the primary socialization agent in shaping children's religious values, which impacts their engagement in school-based religious activities. The research employed a quantitative survey method with a sample of 45 respondents. The data were analyzed using descriptive statistics, validity and reliability tests, normality tests, Pearson correlation, and simple linear regression with the assistance of SPSS software. The results show a strong positive correlation between family religious education and children's interest in religious activities at school (r = 0.721, p < 0.01). Furthermore, family religious education significantly influences children's interest, explaining 52% of the variance in children's interest (R² = 0.520). These findings emphasize the importance of the family's role in supporting and shaping children's religious interest at school as part of ongoing spiritual development.